A retrospective study investigating the clinical significance of body mass index in acute pancreatitis - Bai, Yuanzhen; Gong, Guanwen; Aierken, Reziya; Liu, Xingyu; Cheng, Wei; Guan, Junjie; Jiang, Zhiwei (PeerJ, 2024)
Background Acute pancreatitis is an unpredictable and potentially fatal condition for which no definitive cure is currently available. Our research focused on exploring the connection between body mass index, a frequently overlooked risk factor, and both the onset and progression of acute pancreatitis. Material/Methods A total of 247 patients with acute pancreatitis admitted to Jiangsu Provincial Hospital of Chinese Medicine from January 2021 to February 2023 were retrospectively reviewed. After screening, 117 patients with complete height and body weight data were selected for detailed assessment. Additionally, 85 individuals who underwent physical examinations at our hospital during this period were compiled to create a control group. The study received ethical approval from the ethics committee of Jiangsu Province Hospital of Chinese Medicine (Ref: No.2022NL-114-02) and was conducted in accordance with the China Good Clinical Practice in Research guidelines. Results A significant difference in body mass index (BMI) was observed between the healthy group and acute pancreatitis (AP) patients (p < 0.05), with a more pronounced disparity noted in cases of hyperlipidemic acute pancreatitis (p < 0.01). A potential risk for AP was identified at a BMI greater than 23.56 kg/m2 (AUC = 0.6086, p < 0.05). Being in the obese stage I (95%CI, [1.11–1.84]) or having a BMI below 25.4 kg/m2 (95%CI, [1.82–6.48]) are identified as risk factors for adverse AP progression. Moreover, BMI effectively predicts the onset of acute edematous pancreatitis and acute necrotizing pancreatitis (AUC = 0.7893, p < 0.001, cut-off value = 25.88 kg/m2). A higher BMI correlates with increased recurrence rates within a short timeframe (r = 0.7532, p < 0.01). Conclusions Elevated BMI is a risk factor for both the occurrence and progression of AP, and underweight status may similarly contribute to poor disease outcomes. BMI is crucial for risk prediction and stratification in AP and warrants ongoing monitoring and consideration.
Keywords: Body mass index; Acute pancreatitis; Obesity; Severity; Predictor